2018
DOI: 10.1177/0276236618809670
|View full text |Cite
|
Sign up to set email alerts
|

Everyday (Imagined) Talk: An Exploration of Everyday Conversational Topics and Imagined Interaction Features

Abstract: Imagined interactions (IIs), a cognitive process generating mental imagery of conversations, play an important role in interpersonal relationships. This study investigates the frequency of everyday topics of talk represented in imagined talk and the bivariate and multivariate associations with the features of II functions and II attributes. Participants ( N = 264) reported their general tendencies using II features and general frequency of topics of everyday talk in IIs in a cross-sectional survey. Bivariate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Arvidsson (2006) expounds on the capability of imagination in digital dating, "It is suggested that such 'fantasy work'the work of imagining situations, people, and relationsis activated to an unprecedented extent in the online economy…Dating sites are where the powers of fantasy are stimulated " (p. 672, 678). Imagined interactions (IIs) have similarly been used to describe this type of fantasy/imagination work involved in interpersonal relationships (Honeycutt, 2003(Honeycutt, , 2010(Honeycutt, , 2020LeFebvre et al, 2021;Vickery, 2019) and have a clear use in CMC and digital dating. The present study seeks to apply the interpersonal construct of IIs to CMC, specifically in the realm of online dating, to explore the nature of imagination work while using dating apps and sites.…”
Section: Introductionmentioning
confidence: 99%
“…Arvidsson (2006) expounds on the capability of imagination in digital dating, "It is suggested that such 'fantasy work'the work of imagining situations, people, and relationsis activated to an unprecedented extent in the online economy…Dating sites are where the powers of fantasy are stimulated " (p. 672, 678). Imagined interactions (IIs) have similarly been used to describe this type of fantasy/imagination work involved in interpersonal relationships (Honeycutt, 2003(Honeycutt, , 2010(Honeycutt, , 2020LeFebvre et al, 2021;Vickery, 2019) and have a clear use in CMC and digital dating. The present study seeks to apply the interpersonal construct of IIs to CMC, specifically in the realm of online dating, to explore the nature of imagination work while using dating apps and sites.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research also suggests gender differences, with women having more frequent IIs with a greater variety of topics (Honeycutt et al, 2016). Conversations about love are considered the most frequent topic of IIs, further suggesting the prominence of IIs in instances of potential romantic relationships (Vickery, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior scholarship has primarily observed mental imagery processes in intrapersonal and interpersonal contexts directing empirical applications towards description and explanation. IIs are created and sustained in the mind of one communicator (Vickery, 2019) and involve communication with a real person (Edwards et al., 1989). By engaging in the mental imagery process, individuals practice, (re)conceptualize, and/or change prior communicative experiences.…”
Section: Imagined Interaction (Ii)mentioning
confidence: 99%